2007
DOI: 10.2514/1.24471
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Thermal Model of Circular Foil Heat Flux Gauges

Abstract: This paper presents the solution to a nonlinear model of a circular foil heat flux gauge that is exposed to a blackbody source in a vacuum environment. This is the scenario typically used to calibrate a circular foil heat flux gauge. The nonlinear model is solved using a Green's function approach. This approach results in an integral equation for the steady-state temperature profile in the gauge, which is solved using the method of successive approximations. A relationship between the incident radiative heat f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Circular foil heat flux gauges can be modeled as radiating annular fins. Liechty et al [8] presented a thermal model of a copperconstantan circular foil heat flux gauge exposed to a blackbody source in a vacuum environment. Such a setup is typically used to calibrate a heat flux gauge.…”
Section: Example 1 Radiating Annular Finmentioning
confidence: 99%
See 2 more Smart Citations
“…Circular foil heat flux gauges can be modeled as radiating annular fins. Liechty et al [8] presented a thermal model of a copperconstantan circular foil heat flux gauge exposed to a blackbody source in a vacuum environment. Such a setup is typically used to calibrate a heat flux gauge.…”
Section: Example 1 Radiating Annular Finmentioning
confidence: 99%
“…Fig. 1 shows a comparison of the dimensionless temperature profiles calculated from Equation (14) to those found using the Green's function method used by Liechty et al [8] and to those found from a direct numerical solution using commercial software [28] for various values of the parameters A and B. The accuracy and computational requirements of the method of variation of parameters were compared to those of finite difference methods.…”
Section: Example 1 Radiating Annular Finmentioning
confidence: 99%
See 1 more Smart Citation